2013
DOI: 10.2463/mrms.2012-0063
|View full text |Cite
|
Sign up to set email alerts
|

Rapid High Resolution MR Neurography with a Diffusion-weighted Pre-pulse

Abstract: Purpose: To introduce, optimize, and assess the feasibility of a new scheme to rapidly acquire high-resolution volumetric neurographic images using a three-dimensional turbo spin-echo sequence combined with a diŠusion-weighted pre-pulse called improved motionsensitized driven equilibrium (iMSDE): DiŠusion-prepared MR Neurography (D-prep MRN).Methods: In order to optimize the signal suppression of blood vessels and muscle at Dprep MRN, coronal lumbosacral plexus images were acquired inˆve volunteers at 3T, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
68
0
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(71 citation statements)
references
References 14 publications
1
68
0
2
Order By: Relevance
“…Finally, the present T2 preparation did not use flow or diffusion encoding gradients, thus giving rise to potential signal contamination by surrounding CSF and vessels. The T2 preparation modules with flow or diffusion encoding gradients could be used in the future to remove CSF and vessel signal contamination [5,7,21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, the present T2 preparation did not use flow or diffusion encoding gradients, thus giving rise to potential signal contamination by surrounding CSF and vessels. The T2 preparation modules with flow or diffusion encoding gradients could be used in the future to remove CSF and vessel signal contamination [5,7,21].…”
Section: Discussionmentioning
confidence: 99%
“…In this context, 3D turbo spin echo (TSE) or 3D fast spin echo (FSE) are most commonly used for achieving isotropic high-resolution T2-weighted nerve imaging in or near a plexus [2][3][4]. Furthermore, fat-suppressed 3D TSE imaging has recently been combined with the improved motion sensitized driven equilibrium (iMSDE) preparation to suppress vessel signal and improve plexus nerve delineation [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…We excluded reviews, spinal cord studies and animal or in vivo studies. Our review identified a total of 35 articles: 24 DTI studies and 11 diffusionweighted MR neurography studies [31][32][33][34][35][36][37][38][39][40][41] . The number of lumbar nerve DTI studies has sharply increased in recent years ( Fig.…”
Section: Trends In Clinical Mr Neuroimaging Of Lumbar Nervesmentioning
confidence: 99%
“…Echo spacing = 4 msec, maximum flip angles = [100°, 125°], six start‐up echoes, field of view (FOV) = 400 × 400 × 80 mm 3 , acquisition voxel = 1.25 × 1.25 × 1.4 mm 3 , reconstruction voxel = 0.63 × 0.63 × 0.7 mm 3 , TR/TE = 2000/330 msec, echo train length = 150, duration of each 3D TSE scan = 4 minutes 26 seconds, reference tissue relaxation times T 1 = 1010 msec and T 2 = 90 msec, parallel imaging with reduction factor R = 2.5, no partial Fourier, fat suppression using spectral inversion recovery. Similar to current work in MR neurography with 3D TSE, a T 2 preparation module with two refocusing pulses and with four bipolar velocity encoding gradients was placed before readout to increase nerve–muscle contrast and to reduce vessel signal. The module was employed with TE prep = 29 msec and encoding velocities = 1 cm/s along all three gradient axes.…”
Section: Methodsmentioning
confidence: 99%